Systems of control over set-valued trajectories with terminal quality criterion - Arsirii, A. V.; Plotnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider the optimal control problem with terminal quality criterion in which the state of a system is described by a set-valued mapping, and an admissible control is a summable function. We describe an algorithm that approximates the admissible control function by a piecewise-constant function and prove theorems on the closeness of the corresponding trajectories and the values of quality criteria.